Oxford illustrated encyclopedia: Vol.3 - World history to 1800 (Oxford Univ. Press, 1993)
The book presents history of the world from prehistory through all the most significant developments, events, and ideas in the recorded history of the world up to the end of the 18th century. It contains a wealth of material on ancient civilizations, the classical world, Europe, Africa, the Americas, the Indian sub-continent, and the Middle and Far East